Comparison of Boiling Methods for Bacterial DNA Isolation Using Waterbath and Heatblock - Sirwati, Fadila; Nurfalinda, Siti; Salsabila, Siti; Putri, Dwi (Jurnal Serambi Biologi, 2024)
Molecular biology analysis has several advantages over culture approaches, including the ability to identify a wider range of target organisms, increased sensitivity and specificity. Bacterial DNA isolation is a simple solution in molecular biology analysis. Boiling techniques using high temperature heating can damage cell wall permeability. Heating boiling technique can be done by using waterbath, and heat block with different heat transfer mechanism. The results showed the concentration value of samples isolated using headblock was in the range of 77.6 ug/ul - 200.45 ug/ul, while the concentration of samples isolated using waterbath was in the range of 145.575 ug/ul - 288.8 ug/ul. The highest DNA concentration was obtained from using a waterbath. Purity values measured at wavelengths A260/A280 were obtained with a range of purity that was not different.